2016
DOI: 10.21776/ub.rjls.2016.003.01.3
|View full text |Cite
|
Sign up to set email alerts
|

Biofilter Application Using Seaweed (Gracillaria verucosa) to Increase Production of Vannameii Shrimp in Traditional Pond District Bangil-Pasuruan

Abstract: The aims of this research were to know how to operate and develop the Vannamei production by using biofilter technology of seaweed to the farmer, keeper, young people and leader of the society. The results showed that the Integration of Gracilaria verucosa as a biofilter agent in aquaculture pond can increase the production of Vanname shrimp. The results were obtained 5 tons/ha of seaweed from the initial density of seaweed 1 ton/ha after 3 months of culture with daily growth rate of 4.18%/day. Vannamei shrimp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…Seaweed utilization in biofilter and bioremediator have been widely studied, such as Ulva, Palmaria palmata, Gracilaria, Kappaphycus, and Hypnea aspera (Tremblay-Gratton et al 2018;Laramore et al 2018;Neori et al 2003;Marinho-Soriano et al 2009;Andayani et al 2016;Adharini & Trianti 2020;Castelar et al 2015;Anibal et al 2013;Carneiro et al 2011;Elizondo-González et al 2018;Ribeiro et al 2017;Kang et al 2011;Hayashi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed utilization in biofilter and bioremediator have been widely studied, such as Ulva, Palmaria palmata, Gracilaria, Kappaphycus, and Hypnea aspera (Tremblay-Gratton et al 2018;Laramore et al 2018;Neori et al 2003;Marinho-Soriano et al 2009;Andayani et al 2016;Adharini & Trianti 2020;Castelar et al 2015;Anibal et al 2013;Carneiro et al 2011;Elizondo-González et al 2018;Ribeiro et al 2017;Kang et al 2011;Hayashi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This could be considered the optimal feeding rate in co-culture of L. vannamei with G. tenuistipitata. Several findings revealed that the presence of red seaweed Gracilaria species in shrimp ponds not only improved water quality but also enhanced the survival and growth of shrimp [7,9,11,19]. Besides serving as a bio-filter, Gracilaria served as a natural food source and shelter for fish…”
Section: Survival Productivity and Feed Efficiencymentioning
confidence: 99%
“…Oceanography & Fisheries Open access Journal and shrimp from predators as well as reduction of conspecific cannibalism of shrimp during molting [2,9,19].…”
mentioning
confidence: 99%
“…Gracilaria is economically important as a major source of agar, traditional medicine, human food, and animal feed (Peng, Hong‐Bo, Di, & Song, 2009). It also possesses high biofiltration capabilities that can improve water quality and the production of aquaculture through integrated aquaculture systems (Andayani, Yuwanita, & Izzah, 2016; Anh, An, Lan, & Hai, 2019; Ihsan, Subiyanto, Tri, & Schulz, 2019; Yang et al, 2015). Green seaweed Enteromorpha are distributed throughout the world, in a wide variety of environments from freshwater to seawater, including ocean coast, brackish waters, and inland in freshwater (Bäck, Lehvo, & Blomster, 2000; Romano et al, 2003).…”
Section: Introductionmentioning
confidence: 99%